ANALYSIS OF PROJECT ENFORCEMENT DELAYS WITH THE EARNED VALUE METHOD: (Case study: Office of Bahtera Elang Perak Indonesia Surabaya) - Nailufar, Linda; Witjaksana, Budi; Wulandari , Esti (Transpublika Publisher, 2024)
The construction of the Bahtera Elang Perak Indonesia (BEPI) Office is one of the ongoing projects in Surabaya City consisting of 8 floors with an area of 1,081 m² and a contract value of Rp. 13,908,226,157.00. The Bahtera Elang Perak Indonesia office construction project is planned to last for 43 weeks. In reality, when the piling work is in progress, there are several changes so that there is a need for rescheduling or re-schedulling. The length of implementation time became 54 weeks. The current condition of the progress of the construction of the Bahtera Elang Perak Indonesia Surabaya office is in week 37 at 35.67% while the planned progress is 43.619% so that there is a difference of -7.948%. In order to address this issue, an evaluation of the project's cost and time efficiency during implementation is conducted utilizing the Earned Value Method. This strategy seeks to assess the project's performance in terms of both cost and time. The analysis conducted in week 41 revealed that the performance of the project, in terms of cost, was below expectations with a CPI value of 0.945, indicating that the actual costs exceeded the budgeted costs. Additionally, the CV value of Rp. -381,606.94 further confirmed this negative deviation. In terms of time, the project also experienced delays, as indicated by an SPI value of 0.758, which is less than 1. The SV value of Rp. -2,082,524,745 further highlighted this delay, indicating that the completed work packages were fewer than planned.